A Comparative Study of Direct and Indirect Learning Strategies in Teaching Countable and Uncountable Nouns to Students of SMP Negeri Pauh - Anggun Mahesti; Puji Lestari; Herlan Aryanto; Masagus Firdaus (English Education and Literature Journal (E-Jou), 2026)
Mastery of grammar is a fundamental component of English language acquisition, particularly in understanding countable and uncountable nouns, which frequently pose challenges for junior high school students in producing grammatically accurate sentences. Students’ difficulties in applying appropriate quantifiers, articles, and plural forms demonstrate that this grammatical area has not yet been comprehensively mastered. In response to this issue, the present study examined the effectiveness of direct and indirect learning strategies in enhancing students’ comprehension of countable and uncountable nouns. Employing a quantitative, quasi-experimental design, the study involved two experimental groups of 30 students each. Data were gathered using pre- and post-test instruments and subsequently analyzed using statistical tests, tests of normality and homogeneity, and paired and independent-samples t-tests. The findings indicated that both groups demonstrated statistically significant improvement following the treatments, as reflected in increased mean scores and paired-sample t-test results with p-values below 0.05. Nevertheless, the independent-samples t-test revealed no statistically significant difference between the two instructional approaches, as the p-value exceeded 0.05, suggesting that both direct and indirect learning strategies were comparably effective in improving students’ grammatical understanding. These results imply that integrating both approaches may enhance students’ grammar mastery while also providing teachers with greater pedagogical flexibility in classroom instruction. Consequently, educators are recommended to implement a balanced combination of instructional strategies to achieve more optimal learning outcomes